Cytologic Features of Giant Cell Ependymoma: A Case Report and Review of the Literature - Koh, Myoung Ju; Yoon, Sun Och; Jeon, Hyae Min; Jeong, Hyeon Joo; Hong, Soon Won; Kim, Se Hoon (Journal of pathology and translational medicine, 2012)
Here, we present a case of anaplastic giant cell ependymoma (GCE) occurring in a 15-year-old woman. Squash smear slides for intraoperative frozen section diagnosis revealed oval to round cell clusters with a papillary structure in a fibrillary background. This was occasionally accompanied by the presence of bizarre pleomorphic giant cells with hyperchromatic nuclei and prominent intranuclear inclusions. These intranuclear inclusions were a key clue to diagnosis of ependymoma. Histologic analysis revealed features of a high-grade tumor with perivascular pseudorosettes and bizarre pleomorphic giant cells, which established the diagnosis of GCE. We performed a review of literatures about the cytologic features of GCE, including our case, thus proposing that intraoperative frozen diagnosis of GCE would be established by squash smear preparations featuring the mitosis and necrosis, as well as the high cellularity, and the presence of giant cells showing hyperchromatic nuclei with eosinophilic cytoplasm and intranuclear inclusions/pseudoinclusions.